Comparative Analysis of the Properties of Synthetic and Natural Leathers: A Focus on Microfiber Synthetic Leather for Footwear Applications - Kanwal, Ayesha; Şengün, İpek and Başlar, Atilla and Muhammad Anwaar Nazeer and Acar, Murat and Ioanid, Alexandra and Uzun, Muhammet (European Journal of Sustainable Development, 2025)
The market for leather-like materials has grown significantly due to concerns about natural leather. Research into sustainable materials is an important part of sustainable fashion. This ever-increasing demand for leather alternatives, particularly microfibre synthetic leather, has made it necessary to understand the properties of leather and leather-like materials. Therefore, this study provides a comparative analysis of the properties of natural leather, PU leather and microfibre synthetic leather. The results show that microfibre synthetic leather is the most robust of the three, with adequate seam strength. On the other hand, PU leather has exceptional seam strength and adequate durability compared to natural leather. In addition, further tests were carried out to assess the performance and potential of microfibre synthetic leather for use in footwear. The results demonstrated the resilience of the material and its potential to improve product durability and sustainability. Considering the test results, it is thought that microfibers will contribute to the concept of environmentally friendly fashion with a longer lifetime and therefore less consumption. It is also thought that both long usage and low structural deformation will increase the intensity of use of these structures in the fashion industry. Keywords: synthetic leather, natural leather, footwear